MICRONUTRIENT INTAKE AND PERCEIVED BARRIERS AMONG ANAEMIC PREGNANT WOMEN IN ACEH, INDONESIA - Nahrisah, Putri; Plianbangchang, Samlee; Somrongthong, Ratana; Kumar, Ramesh; Wahed, Tasnuva; Anwar, Fozia (Journal of Ayub Medical College Abbottabad, 2019)
Background: Estimating vitamin, mineral intakes related to anaemia and describing perception regard pregnancy diet, accessibility to foodstuff among first ANC visitor of anaemic pregnant women aged above 20 years in Province Aceh, Indonesia. Methods: A cross sectional mix-method of quantitatively and focus group discussion (FGD) was conducted at two municipalities having more than 40% anaemic pregnancy. One hundred fifty-eight anaemic pregnant women were interviewed regarding socio-demographic and three days of 24-hours food recall, in addition to FGD at each municipality using FGD guidelines about nutritional anaemia. Food recall data was analysed using software NutriSurvey Indonesia, deficiency is defined as daily intake below 77% recommended dietary allowances (RDA) Indonesia. The FGD result was analysed by content analysis and clarified with representative quotes. Result: Prevalence of deficiencies intake were folate (98.7%), vitamin B6 (91.1%), vitamin B2 (90.5%), iron (89.2%), zinc (87.3%), vitamin E (84.8%), vitamin C (79.7%), vitamin A (74.1%), copper (67.1%) and vitamin B12 (30.4%). Anaemic pregnant women noticed to consume more amount of food during pregnancy, and preferred to access foodstuff at shop nearby the house. Conclusion: Other than low iron intake, more than 90% anaemic pregnant women were also deficiency in folate, vitamin B6 and vitamin B2. Perceived of less acknowledgement about affordable cost micronutrient-rich food, high cost of quality-food, sufficient to varieties foodstuff at neighbourhood shop prevents them from making correct food choices subsequently barrier to the food access and intake. Keywords: anaemic pregnancy; vitamin and mineral intake; perception